Model of Quality Balance Development of Bali Tourism Destination - Utama, I Gusti Bagus Rai; Turker, Sidhi Bayu; Widyastuti, Ni Kadek; Suyasa, Ni Luh Christine Prawita Sari; Waruwu, Dermawan (Technium Social Sciences Journal, 2020)
the economic structure of Bali Province is very specific and has its characteristics compared to other provinces in Indonesia. This can be seen from the contribution of value-added to the economic sector, which is largely dominated by the tertiary sector, especially the tourism services sub-sector which has become the backbone of economic growth followed by the primary sector and the secondary sector. The dominance of the tertiary sector has the potential to be very risky because the tourism sector is very vulnerable to various phenomena including the Covid-19 pandemic. The debate between the purpose of preservation and economic empowerment in cultural tourism with all its manifestations is still a heated debate among tourism experts and tourism businesses. While the development of Bali tourism from time to time has experienced many changes along with the social dynamics that exist in society Bali. This study uses method desk research by conducting a study of literature related to the problem being solved, through a study of scientific journals, opinions, and online articles, then comparing and finding similarities and differences so that it can be used to explain the problem you want to solve. In the discussion of this study, it was found that there was still dualism that needed to be integrated to create a balance between the goals of cultural preservation and economic development for Bali. There are several solutions offered; such as Picard offers solutions to the understanding and function of art and culture and its activities in tourism and religious life. While Max-neef offers Tourism community relationships, while other solutions are the need for stakeholder involvement, Blueprint, and Carrying Capacity